MicroRNA-99a Suppresses Breast Cancer Progression by Targeting FGFR3 - Long, Xinghua; Shi, Yu; Ye, Peng; Guo, Juan; Zhou, Qian; Tang, Yueting (Frontiers in Oncology, 2020)
MicroRNAs have been implicated in acting as oncogenes or anti-oncogenes in breast cancer by regulating diverse cellular pathways. In the present study, we investigated the effects of miR-99a on cell biological processes in breast cancer. breast cancer cells were transfected with a lentivirus that expressed miR-99a or a scramble control sequence.Functional experiments showed that miR-99a reduced breast cancer cell proliferation, invasion and migration. Tumor xenograft experiment suggested miR-99a overexpression inhibited breast cancer cell proliferation in vivo. The dual luciferase assay revealed that miR-99a directly targets FGFR3 by binding its 3' UTR in breast cancer. miR-99a was strongly down-regulated in breast tumor and FGFR3 was significantly up-regulated in breast tumor. FGFR3 silencing inhibited proliferation, migration and invasion of breast cancer cells. Deep sequencing indicated that miR-99a overexpression regulates multiple signaling pathways and triggeres the alteration of the whole transcriptome. We constructed correlated expression networks based on circRNA/miRNA and lncRNA/miRNA competing endogenous RNAs regulation and miRNA-mRNA interaction, which provided new insights into the regulatory mechanism of miR-99a. In conclusion, these results suggest that the miR-99a/FGFR3 axis is an important tumor regulator in breast cancer and might have potential as a therapeutic target.